Biogeochemical and ecosystem properties in three adjacent semi‐arid grasslands are resistant to nitrogen deposition but sensitive to edaphic variability. (24th May 2022) - Osborne, Brooke B.; Roybal, Carla M.; Reibold, Robin; Collier, Christopher D.; Geiger, Erika; Phillips, Michala L.; Weintraub, Michael N.; Reed, Sasha C.
Abstract: Drylands have low nitrogen stocks and are predicted to be sensitive to modest increases in reactive nitrogen availability, but direct evidence that atmospheric nitrogen deposition will have sustained effects on dryland ecosystems is sparse and conflicting. We used three long‐running in situ nitrogen deposition simulation experiments and a complementary laboratory incubation experiment to address fundamental questions about how nitrogen inputs affect drylands: (1) What are the long‐ and short‐term consequences of nitrogen inputs for biogeochemical and ecosystem properties?; (2) Do these consequences depend on soil moisture availability?; and (3) Does soil texture modify the effects of nitrogen inputs and/or soil moisture availability? In 2011, we established three study sites along a soil texture gradient in Arches National Park with plots receiving 0, 2, 5 or 8 kg N ha −1 annually ( n = 5 per treatment per site). We assessed a suite of biogeochemical metrics over the long term and short term. To assess longer term effects, we sampled annually (2013–2019), just prior to spring nitrogen fertilization. To assess short‐term effects, we sampled immediately before and after spring nitrogen fertilization in 2013. Additionally, we compared foliar chemistry, soil extracellular enzyme activities, heterotrophic respiration rates, and nitrogen trace gas fluxes at select intervals during the study period (2011–2019). Finally, we conducted a laboratory incubation to measure the individual and interacting effects of soil moisture and nitrogen additions on soil microbial activity. We identified some short‐term effects in situ, but no lasting consequences of added nitrogen for any of the metrics measured. In the incubation, soil moisture treatments independently increased heterotrophic respiration rates but did not modify the effects of added nitrogen. In contrast to nitrogen treatments, soil texture was associated with large differences in biogeochemical cycling. Our results oppose the common prediction that coupled dryland biogeochemical cycles are sensitive to nitrogen inputs and suggest that fine‐scale edaphic heterogeneity is a key driver of dryland ecosystem properties. Synthesis . This study synthesizes a rare, long‐term dataset, which provides robust evidence that carbon and nutrient cycling and availability are resistant to realistic levels of atmospheric nitrogen deposition in remote dryland ecosystems. Abstract : This study synthesizes a large, diverse dataset from three long‐running nitrogen deposition simulation experiments (2011–2019), which provides robust evidence that carbon and nutrient cycling and availability are resistant to realistic levels of atmospheric nitrogen deposition in remote dryland ecosystems. We identified some short‐term effects on biogeochemical and ecosystem properties, but no lasting consequences of added nitrogen in any of the metrics measured.